2007
DOI: 10.1302/0301-620x.89b3.18123
|View full text |Cite
|
Sign up to set email alerts
|

Benign solitary schwannomas

Abstract: We reviewed 234 benign solitary schwannomas treated between 1984 and 2004. The mean age of the patients was 45.2 years (11 to 82). There were 170 tumours (73%) in the upper limb, of which 94 (40%) arose from the brachial plexus or other nerves within the posterior triangle of the neck. Six (2.6%) were located within muscle or bone. Four patients (1.7%) presented with tetraparesis due to an intraspinal extension. There were 198 primary referrals (19 of whom had a needle biopsy in the referring unit) and in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
151
0
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(173 citation statements)
references
References 11 publications
0
151
0
16
Order By: Relevance
“…She did not return for check-ups in our department, nor did she ever present to the oncology department requesting treatment. [4,5] . They usually grow slowly and eccentrically to the nerve fibre, and are thus encapsulated by the perineurium [4] .…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…She did not return for check-ups in our department, nor did she ever present to the oncology department requesting treatment. [4,5] . They usually grow slowly and eccentrically to the nerve fibre, and are thus encapsulated by the perineurium [4] .…”
Section: Case Presentationmentioning
confidence: 99%
“…They usually grow slowly and eccentrically to the nerve fibre, and are thus encapsulated by the perineurium [4] . Most cases develop between 20 and 50 years of age, with equal sex distribution, the most affected sites being the head and neck and the flexor surface of the extremities [4,5] . Macroscopically, schwannomas are well circumscribed, round or oval whitish solid tumours, while microscopically they present a biphasic pattern with areas of highly organized spindle cells (Antoni A area) and less organized, hypocellular areas where myxoid tissue predominates (Antoni B area), surrounded by a true capsule.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwannomas can occur in isolation or as part of syndromes such as neurofibromatosis I and neurofibromatosis II. In 73% of cases, solitary benign schwannomas affect the upper limbs [2]. They can also appear in other areas, for example, on the inner thoracic wall [3], the retroperitoneum [4], or the orbita [5].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 24 patients with lower limb schwannomas only 3 developed a Grade 3 motor deficit. Knight et al [17] found 28 patients to have neurological deficit and/or pain after excision of schwannomas. Factors to try to reduce the neurological deficit include; avoiding unnecessary biopsy, air tourniquet use for good vision under microscope, intracapsular approach, limited incision of the epineurium, atraumatic dissection, no en bloc resection if traumatic, adequate drainage to prevent hematoma formation and to raise the affected limb.…”
mentioning
confidence: 99%